Velocidade terminal: tempo cronoscópico dos corpos orbitais na composição sonora e musical - Paquete, Hugo (2021)
This essay presents the construction processes, methodologies, meanings and challenges in the construction of the Dromology of Orbital Bodies project of my own developed between 2019-2020 and which is still ongoing. The project aims to track military and commercial satellites by converting that information in real time by sonicating the date received from the hacked satellite. Therefore, this essay presents the technical challenges in the habit of building the conditions of the project as well as some of the results obtained. Also presenting the dimension of meanings associated with the project from a philosophical and critical point of view, in a combination of conceptual reflection and project exploration where concepts such as chronoscopic time, cyberpunk, and gray colony and acoustemology are related as a reading of a time where the sonorous happens mediated by technology. These concepts influence the production, composition and musical performance processes that I develop with special interest in systems where unpredictability operates alongside real-time relationships and systems, using granularisation and a sound and compositional aesthetic historically informed in noise and micro. post-digital rhythmic.